Exploring gender differences in self-confidence related to entering the workforce among Muslim college students - Indra, Syaiful; Fitri, Silvia; Azhari, Azhari; Mahdi, Mahdi; Sujadi, Eko; Andriyani, Juli (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2024)
Self-confidence is an essential component of an individual's psychological well-being, shaped by various factors, including gender. While differences in self-confidence exist, both men and women seek positive self-understanding to navigate life's challenges. Recognizing these differences is crucial for supporting the development of healthy and positive self-confidence. This study investigates the self-confidence levels of male and female students and compares their confidence in entering the workforce. Utilizing a quantitative descriptive approach, the study found that, on average, women exhibited higher levels of self-confidence than men. However, the comparison of self-confidence regarding entry into the workforce revealed no significant gender differences. These findings suggest that the educational environment fosters equal conditions, preparing students to face career challenges irrespective of gender. This research emphasizes the importance of an inclusive and equitable educational approach, where the development of relevant skills and competencies for the workforce is prioritized alongside the enhancement of self-confidence, a vital factor in achieving professional success. The implications of this study contribute to career counseling services in higher education, highlighting the need to focus on gender-neutral strategies that build students' self-confidence and equip them for future professional roles.